The impact of the Hunga Tonga-Hunga ha’apai volcanic eruption on the 2023 Antarctic Ozone hole, as observed from Arrival Heights, Antarctica - Smale, Dan; Chipperfield, Martyn P.; Querel, Richard; Nedoluha, Gerald E.; Frieß, Udo; Robinson, John; Nichol, Sylvia; Heddell, Saffron; Feng, Wuhu; Gomez, R. Michael; Boyd, Ian; Smale, Penny; et al. (Journal of atmospheric chemistry, 2025)
The Hunga Tonga-Hunga Ha’apai volcanic eruption in January 2022 injected an extraordinary amount of water vapour into the tropical stratosphere (estimated at 150 Tg) along with a modest injection of sulphur dioxide (estimated at 0.4 Tg). Using a suite of ground-based remote-sensing trace gas measurements located at Arrival Heights, Antarctica (78 S, 167E), along with co-located satellite measurements of water vapour and stratospheric aerosol optical depth, we observed the evolution of the 2023 ozone hole. Arrival Heights was located beneath the polar vortex for extended periods during the austral spring (late August to early December) 2023. Within this period, satellite measurements of lower stratospheric water vapour above Arrival Heights fall within climatology norms (2004-2023) while elevated (70% increase in September mean sAOD), but highly variable, levels of stratospheric aerosol optical depth were observed. Ground-based measurements (total and partial columns) of ozone, ClO, HCl, ClONO2, OClO, NO, NO2 and HNO3 throughout springtime show no measurable attributable impact of Hunga Tonga-Hunga Ha’apai water vapour on stratospheric chemical composition, and ozone depletion within the polar vortex. Prolonged denitrification and elevated levels of chlorine monoxide in the second half of September were caused by unseasonally low stratospheric temperatures. Contemporary TOMCAT 3-D chemical transport model simulations are in overall good agreement with observations. The model simulations indicate Hunga Tonga-Hunga Ha’apai water vapour caused an additional reduction in total column ozone of 5 -7 DU over Arrival Heights in spring and early summer within the polar vortex. Such small differences are not discernible using the current measurement dataset given atmospheric variability, measurement precision and observational gaps. The simulations indicate the largest additional reduction in total column ozone were in the polar vortex collar region, where increased water vapour loading caused additional ozone loss up to 13 DU over Arrival Heights.
Online veröffentlicht: 25. August 2025
Gesehen am 18.02.2026